If ^@ x = 1 + \sqrt{ 2 } + \sqrt{ 3 }, ^@ then ^@ x^4 - 4x^3 -4x^2 + 16x = ? ^@


Answer:

^@ 8 ^@

Step by Step Explanation:
  1. Given: ^@ x = 1 + \sqrt{ 2 } + \sqrt{ 3 } ^@
    According to the question, we need to find the value of ^@ x = 1 + \sqrt{ 2 } + \sqrt{ 3 } ^@
  2. ^@ \begin{align} & x = 1 + \sqrt{ 2 } + \sqrt{ 3 } \\ \implies & x - 1 = \sqrt{ 2 } + \sqrt{ 3 } \end{align} ^@
    Taking the square on both sides
    ^@ \begin{align} & x^2 + 1 - 2x = 2 + 3 + 2 \times \sqrt{ 2 } \times \sqrt{ 3 } \space\space\space\space\space [ \text{ Using } (a + b)^2 = a^2 + b^2 + 2ab ] \\ \implies & x^2 - 2x - 4 = 2 \sqrt{ 6 } \\ \end{align} ^@
  3. Again, taking the square on both sides
    ^@ \begin{align} & \space x^4 + 4x^2 + 16 - 4x^3 + 16x - 8x^2 = 4 \times 6 \space\space\space\space\space [\because (a - b - c)^2 = a^2 + b^2 + c^2 -2ab + 2bc -2ca ] \\ & \implies x^4 - 4x^3 -4x^2 + 16x + 16 = 24 \\ & \implies x^4 - 4x^3 -4x^2 + 16x = 8 \\ \end{align} ^@

You can reuse this answer
Creative Commons License

What they say